Palliative care and end of life interventions based on culture, religion and belief: Qualitative - Juwita, Helmi; Prihatini, Surya; Qasim, Muhammad (Institute of Computer Science (IOCS), 2024)
Chemotherapy patients often face great emotional stress. Palliative care interventions by providing psychosocial support help overcome stress, anxiety, and depression that may arise during treatment. In addition to alleviating psychosocial symptoms, alleviating the symptoms of the patient's disease or improving the quality of life of chemotherapy patients also need to be done. The interventions given do not only focus on the patient's bio psychosocial, but interventions related to culture, religion and beliefs are needed for patients. This study aims to determine the palliative care and end of life interventions of nurses based on culture, religion and beliefs in the chemotherapy room of Hasanuddin University Hospital. The research design uses a qualitative research with a purposive sampling technique based on inclusion criteria. The instruments used were interview guidelines related to the theory of peaceful end of life and transcultural nursing theory by considering the cultural, religious and belief aspects of the patient. The results of the study showed that nurses provided interventions for pain, feelings of comfort, feeling dignified, being at peace, closeness to family and close people. Culturally, interventions were carried out by fully involving the family and paying attention to the patient's religion and beliefs in the chemotherapy room.